2019
DOI: 10.1002/nvsm.1637
|View full text |Cite
|
Sign up to set email alerts
|

Organ donation in India—A social marketing perspective

Abstract: Organ donation is a social issue, and marketers face challenges promoting it. If factors aiding and inhibiting it are identified, it becomes easier to enhance intention of donating organs. The objective of this research is to establish the role of perceived awareness, family support, perceived individual value, and religiosity on organ donation intention (ODI). A sample of 247 respondents answered a structured questionnaire. Proposed model is mediated by organ donation attitude (ODA) and moderated by perceived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 101 publications
(143 reference statements)
0
1
0
Order By: Relevance
“…Social marketing contributed to inducing a variety of beneficial behaviors for individuals and society such as reducing smoking and drinking behavior, drug abuse (Stead et al , 2007), HIV infections (Rimal and Creel, 2008), condom use, environmental protection, healthy eating and anti-violence (Helmig and Thaler, 2010). Over time, donation behavior literature began to rely on this approach as well (Brennan and Binney, 2010) and revealed that social marketing can increase organ (Mohan and Aswathy, 2019) and blood donations (Beerli-Palacio and Martin-Santana, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Social marketing contributed to inducing a variety of beneficial behaviors for individuals and society such as reducing smoking and drinking behavior, drug abuse (Stead et al , 2007), HIV infections (Rimal and Creel, 2008), condom use, environmental protection, healthy eating and anti-violence (Helmig and Thaler, 2010). Over time, donation behavior literature began to rely on this approach as well (Brennan and Binney, 2010) and revealed that social marketing can increase organ (Mohan and Aswathy, 2019) and blood donations (Beerli-Palacio and Martin-Santana, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%